Handbook of tribal politics in India - Ambagudia, Jagannath; Xaxa, Virginius (Thousnd Oaks : SAGE Publications India Pvt Ltd, 2021)
"Handbook of Tribal Politics in India is undoubtedly the most authoritative source for a systematic and comprehensive study of this vibrant field of scholarship. Divided into three sections, the chapters cover a broad range of themes ranging from a general introduction to tribal politics to exploring contemporary issues and concerns within the discipline. The book presents a trajectory and authentic overview of tribal politics while keeping in mind the changing relationship between tribal communities and democracy. Using qualitative and quantitative data, it studies the role of tribal political representatives in public policy-making, issues related to communities, and the nature and dynamics of tribal politics at the state and national levels. It explores the patterns, conditions and challenges of tribes' participation in electoral politics and presents the issues and agendas that will continue to affect the tribal politics in future. This book is an essential resource for teaching and research in political science and other social science disciplines studying comparative political dimensions"--
Keywords: Tribes -- Political aspects -- India. -- Tribes -- India -- Politics and government. -- Tribus -- Aspect politique -- Inde. -- India -- Tribes--Politics and government -- Tribes -- Politics and government